Gastric Cancer in Young Adults: A Different Clinical Entity from Carcinogenesis to Prognosis - Li, Jian (Gastroenterology research and practice, 2020)
Approximately 5.0% of gastric cancer (GC) patients are diagnosed before the age of 40 and are not candidates for screening programs in most countries and regions. The incidence of gastric cancer in young adults (GCYA) has declined over time in most countries except in the United States. Genetic alterations, environmental factors, and lifestyle may predispose some young adults to GC. According to molecular classifications, the cancer of most GCYA patients belongs to the genomically stable or microsatellite stable/epithelial-mesenchymal transition subtype, with the common genetic aberrations being mutations in CDH1. What characterizes GCYA are a higher prevalence in females, more aggressive tumor behaviors, diagnosis at advanced stages, fewer comorbidities and being better treatment candidates, and a similar or better survival outcome when compared with older patients. Considering the greater loss of life-years in younger patients, lowering the incidence of GC and diagnosing at a relatively early stage are the two most effective ways to decrease GC mortality. To achieve these goals, the low awareness of GCYA among general people, policy-makers, clinicians, and researchers should be changed.